The Comparison of accountants' expectations and availability in entrepreneurial perspectives after opening ASEAN Economy Community - PHENGSAVAT, Sitthivikone; SOMSACKXAYSOMPHENG, Oulavieng; PHOUNNALY, Phayvanh; NORCHANDA , Sithone; INTHAVICHIT , Lattana (Souphanouvong University Journal Multidisciplinary Research and Development, 2021)
This research is intende to study “The comparison of accountant’s expectations availability level in entrepreneurial perspectives after opening ASEAN Economy Community (AEC) divided by personal factors”. The sample used in this research are entrepreneurial businesses, LuangPrabang province using simple sampling technigue whith the total number of totally 151 business owners. The statistics used in data analysis includes descriptive and referential parameters statistic in cluding : frequency, percent, average, standard deviation, T-tests and single test variability (One Way ANOVA) And paired testing by LSD method. The results of the research were found that: (1) The comparison of accountants' expectations levels in entrepreneurial perspectives after launching AEC when divided by type of entrepreneurial gender revealed that different genders bring two different expectations levels, including legal knowledge and information technology. When classified by age, two different expectations were discovered, such as professional accounting and legal knowledge. When classified by educational background, it was revealed that entrepreneurs with different educational backgrounds have one different expectation in foreign languages, and entrepreneurs with different working experiences have three different expectations, such as accounting professional, legal knowledge, and knowledge of ASEAN member countries.(2) The comparison of accountants' availability levels in entrepreneurial perspectives after launching AEC when divided by type of entrepreneurial gender revealed that different genders bring two different expectations levels, including foreign languages and knowledge of ASEAN member countries. (3) When comparing the level of accountants' expectations and availability in entrepreneurial perspectives after opening AEC, there are four levels of difference: foreign languages, legal knowledge, knowledge of ASEAN members, and information technology.